The forever dog life : 120+ recipes, longevity tips, and new science for better bowls and healthier homes - Becker, Karen Shaw; Habib, Rodney (Harper, an imprint of HarperCollinsPublishers, 2024)
"In this guide, the authors of the #1 internationally bestselling The Forever Dog show how to create a healthy, sustainable lifestyle and environment to help your dog live a longer, happier, and healthier life"--